Characterization of interactions of eggPC lipid structures with different biomolecules - Corrales Chahar, F. (2018)
In this paper we study the interactions of two biomolecules (ascorbic acid and Annonacin) with a bilayer lipid membrane. Egg yolk phosphatidylcholine (eggPC) liposomes (in crystalline liquid state) were prepared in solutions of ascorbic acid (AA) at different concentration levels. On the other hand, liposomes were doped with Annonacin (Ann), a mono-tetrahydrofuran acetogenin (ACG), which is an effective citotoxic substance. While AA pharmacologic effect and action mechanisms are widely known, those of Ann's are only very recently being studied. Both Fourier Transformed Infrared (FTIR) and Raman spectroscopic techniques were used to study the participation of the main functional groups of the lipid bilayer involved in the membrane-solution interaction. The obtained spectra were comparatively analyzed, studying the spectral bands corresponding to both the hydrophobic and the hydrophilic regions in the lipid bilayer. Electrochemical experiments namely; impedance spectroscopy (EIS) and cyclic voltamperometry (CV) were used as the main characterization techniques to analyse stability and structural changes of a model system of supported EggPC bilayer in connection with its interactions with AA and Ann. At high molar ratios of AA, there is dehydration in both populations of the carbonyl group of the polar head of the lipid. On the other hand, Ann promotes the formation of hydrogen bonds with the carbonyl groups. No interaction between AA and phosphate groups is observed at low and intermediate molar ratios. Ann is expected to be able to induce the dehydration of the phosphate groups without the subsequent formation of H bonds with them. According to the electrochemical analysis, the interaction of AA with the supported lipid membrane does not alter its dielectric properties. This fact can be related to the conservation of structured water of the phosphate groups in the polar heads of the lipid. On the other hand, the incorporation of Ann into the lipid membrane generates an increase in the number of defects while changes the dielectric constant. This, in turn, can be associated with the induced dehydration of the phosphate groups.